Analysis of Connected Arrays and Capacitively Coupled Arrays - Seyed Mahdi Hosseini; Zahra Atlasbaf (IEEE Access, 2022)
The concept of connected and capacitively coupled dipoles in a planar array, which improves wideband performance, is investigated. A long wire with multiple feeds acts as an array in connected arrays, whereas a capacitively coupled array uses capacitors between array elements. Both approaches attempt to approximate the current sheet of Wheeler. Using spectral Green’s function, the array active impedance is calculated. The impedance mismatch of a connected/capacitively coupled dipole array is less than that of an array of unconnected dipoles of the same size. Both direct and capacitive connections can be used to design a wideband array antenna with a ground plane, although capacitive coupling performs better than a direct connection. This fact resulted from numerous analytical studies using infinite dipole array scan (active) impedance endorsed by full-wave simulations using CST MWS. The maximum mismatch losses over the frequency band for different source (reference) impedances are used to find the best solution at the broadside. The average reflected power over all scan angles is applied, for the scan performance, and then, the maximum average mismatch loss over the frequency band is investigated.